Optimization of Gas Turbine Component Maintenance to Improve Reliability of Power Plant Industries - Dharmawan, Doni Ardhi; Suef, Mokh. (IPTEK Journal of Proceedings Series, 2020)
he thermal power plant unit in Java is PLTGU Z with 3 blocks consisting of 9 gas turbines, and 3 steam turbines with a total installed capacity of 1578.78 MW. One of the problems faced is a high component failure rate, decreased system reliability, and an impact on rising maintenance costs. The method to be implemented in order to maintain the achievement of power plant performance and reliability of generating units is to optimize equipment reliability. Periodic component replacement is one way to maintain the reliability of the unit, where current conditions do not yet exist as a standard that is specifically used as a basis for the component replacement activities. For this reason, optimization of component replacement is required by considering the value of reliability, equipment downtime, frequency of replacement time, and costs required. It is intended that the reliability of the equipment is achieved at the optimum cost. The first stage is to identify the reliability value based on the failure data using Weibull ++ 6 software, then adjusted to the system reliability target in accordance with company standards. The second stage performs calculations to determine the minimum time of downtime and minimum preventive maintenance costs in a period of time. The third stage is determining the optimization of equipment reliability and the consequence of the required cost increase according to the system reliability target. After optimizing the reliability of the system with a target value of R(G) = 0.7 the optimization results obtained with the longest preventive maintenance intervals on gas nozzle equipment every 8000 hours, and the shortest maintenance time intervals are found on the fuel gas system equipment that is 40 hours.